Chapter Massa Lubrense coast and its modifications during the twentieth century - Bertoli, Barbara (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
This contribution aims to analyse the stages of the anthropogenic activities that have modified some stretches of the Massa Lubrense coast during the twentieth century. The landscape values that had defined the originality and uniqueness of this territory began to be altered; following the mining activities, the coast was literally devoured and modified in its secular structure. The construction of bathing establishments, hotel complexes, private parks not regulated by building plan, has changed definitively the environmental and landscape parameters of this wonderful coast.